Retrospective future thinking as a novel method to imagine the future: remembering autobiographical events from the perspective of the future self. Issue 1 (2nd January 2023) - Roderer, Ayleen; Bohn, Annette
ABSTRACT: People think retrospectively about past events and prospectively about future events. Here, the novel method of retrospective future thinking is introduced to investigate the characteristics of autobiographical events reported as if they had been already experienced. In total, 166 participants were asked to (1) generate cultural life scripts and (2) to imagine themselves being 100-years old. From this perspective, they reported, dated and rated on valence their seven most important events. Results provide evidence that the cultural life script guides the recall and, more so, the imagination of retrospectively reported autobiographical events. Exploratory analysis of age effects indicated that older participants reported events that were more realistic, less scripted and wider distributed across the life span. This provides the first evidence that retrospective future thinking can alter older adults' life perspective by expanding their period for experiencing important events beyond the reminiscence bump years.